Flexible dispatch strategy for electric grid integrating PEM electrolyzer for hydrogen generation - Liao, Minfang; Marocco, Paolo; Gandiglio, Marta; Liu, Chengxi; Santarelli, Massimo (Frontiers in Energy, 2025)
Proton exchange membrane (PEM) electrolyzer (EL) is regarded as a promising technology for hydrogen generation, offering load flexibility for electric grids (EGs), especially those with a high penetration of renewable energy (RE) sources. This paper proposes a PEM-focused economic dispatch strategy for EG integrated with wind-electrolysis systems. Existing strategies commonly assume a constant efficiency coefficient to model the EL, while the proposed strategy incorporates a bottom-up PEM EL model characterized by a part-load efficiency curve, which accurately represents the nonlinear hydrogen production performance, capturing efficiency variations at different loads. To model this, it first establishes a 0D electrochemical model to derive the polarization curve. Next, it accounts for the hydrogen and oxygen crossover phenomena, represented by the Faraday efficiency, to correct the stack efficiency curve. Finally, it includes the power consumption of ancillary equipment to obtain the nonlinear part-load system efficiency. This strategy is validated using the PJM-5 bus test system with coal-fired generators (CFGs) and is compared with a simple EL model using constant efficiency under three scenarios. The results show that the EL modeling method significantly influences both the dispatch outcome and the economic performance. Sensitivity analyses on coal and hydrogen prices indicate that, for this case study, the proposed strategy is economically advantageous when the coal price is below 121.6 $/tonne. Additionally, the difference in total annual operating cost between using the efficiency curve anda constant efficiency to model becomes apparent when the hydrogen price ranges from 2.9 to 5.4 $/kg.